Factors Influencing Online Repurchase Through Satisfaction - Saplina, Faris Saputra; Nazwirman, Nazwirman; Byarwati, Anis (Jurnal Organisasi dan Manajemen, 2020)
This research examines the influence of price fairness and product quality on satisfaction and repurchase on Tokopedia. This is a quantitative research that used Structural Equation Model (SEM) with SPSS and Lisrel software for data analysis. Purposive sampling is used to select samples, though it is limited to certain respondents. The minimum sampling size is 10 times the number of research indicators, with a total 149 respondents analyzed. Findings. The results showed that Price Fairness and Product Quality had significant and positive impacts on satisfaction. Furthermore, Product Quality and Satisfaction have significant and positive effect on repurchase, while Satisfaction mediates price fairness to Repurchase and Product Quality.